2008
DOI: 10.1210/en.2008-0122
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Actions in the Male Reproductive System Involve Estrogen Response Element-Independent Pathways

Abstract: The estrogen receptor-alpha (ERalpha) acts through multiple pathways, including estrogen response element (ERE)-dependent (classical) and ERE-independent (nonclassical) mechanisms. We previously created a mouse model harboring a two-amino-acid mutation of the DNA-binding domain (E207A, G208A) that precludes direct binding of ERalpha to an ERE. After crossing heterozygous mutant mice with an ERalpha knockout (ERKO) line, it was possible to assess the degree of physiological rescue by the isolated ERalpha noncla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Although effects on the efferent ductules were noted as early as 4 days after treatment (Cho et al 2003), effects on the testis were delayed, similar to those seen in the ERaKO (Eddy et al 1996;Hess et al 1997a;Weiss et al 2008), but seminiferous tubular atrophy was heterogeneous and focal, as seen in ArKO mice Robertson et al 2001Robertson et al , 2002Toda et al 2008), and not due to fluid back-pressure. Others have also found apparent direct effects of ICI 182,780 on seminiferous epithelium (Gancarczyk et al 2004;Anahara et al 2006), including effects within 6 days of treatment (Anahara et al 2006).…”
Section: Oestrogens and The Regulation Of Spermatogenesismentioning
confidence: 60%
“…Although effects on the efferent ductules were noted as early as 4 days after treatment (Cho et al 2003), effects on the testis were delayed, similar to those seen in the ERaKO (Eddy et al 1996;Hess et al 1997a;Weiss et al 2008), but seminiferous tubular atrophy was heterogeneous and focal, as seen in ArKO mice Robertson et al 2001Robertson et al , 2002Toda et al 2008), and not due to fluid back-pressure. Others have also found apparent direct effects of ICI 182,780 on seminiferous epithelium (Gancarczyk et al 2004;Anahara et al 2006), including effects within 6 days of treatment (Anahara et al 2006).…”
Section: Oestrogens and The Regulation Of Spermatogenesismentioning
confidence: 60%
“…The intracellular mechanisms of ERs action in the present study and the possible involvement of both ERa and ERb in spermatogenic cell apoptosis are not known, and further studies are required. More recent work has been shown that estrogen action in male reproductive system does not involve EREs pathway (Weiss et al 2008). Moreover, many studies revealed a nongenomic signaling pathway through membrane-associated ERs (Hammes & Levin 2007) and cross-talk between genomic pathways (Revelli et al 1998, Losel et al 2003.…”
Section: Dbp-induced Spermatogenic Cell Apoptosis Is Mediated Via Ersmentioning
confidence: 99%
“…Several previous studies have used ERα mutant knock-in mice to evaluate ERα function in male reproduction (26,27). The E207A, G208A mutated ERα knock-in (NERKI) mice were found to lack ERE-mediated transcription, but allowed E2-dependent transcription by ERα tethering with AP-1 (28).…”
Section: Discussionmentioning
confidence: 99%